The Pengaruh Transaksi Pihak Berelasi terhadap pada Perusahaan Sektor Healthcare di Bursa Efek Indonesia: Pengaruh Transaksi Pihak Berelasi terhadap pada Perusahaan Sektor Healthcare di Bursa Efek Indonesia - Ni Ketut Utami Dewi (Politeknik Raflesia Press, 2026)
This study aims to examine the effect of related party transactions on the Effective Tax Rate (ETR) of Healthcare companies listed on the Indonesia Stock Exchange during the 2021–2025 period. Related party transactions are often associated with tax planning practices because they may provide opportunities for profit shifting within corporate groups. However, empirical evidence regarding their impact on corporate tax burden remains inconclusive. Therefore, this study investigates whether related party transactions influence the Effective Tax Rate while controlling for firm size, leverage, and profitability. This research employs a quantitative approach using secondary data obtained from the annual financial statements of Healthcare companies. The sample was selected using purposive sampling, resulting in 50 firm-year observations. Data were analyzed using multiple linear regression with IBM SPSS Statistics after conducting classical assumption tests. The results indicate that related party transactions do not have a significant effect on the Effective Tax Rate. These findings suggest that related party transactions in Healthcare companies are primarily conducted to support operational activities rather than as a strategy to reduce corporate tax obligations. Among the control variables, profitability has a significant negative effect on the Effective Tax Rate, whereas firm size and leverage do not show significant effects. The model explains 23.7% of the variation in the Effective Tax Rate. This study contributes to the literature by providing empirical evidence that related party transactions are not a significant determinant of the Effective Tax Rate in Indonesian Healthcare companies. Future research is recommended to include additional variables and a broader research scope to better explain variations in corporate Effective Tax Rates.